Oxygen Mass Transfer in an Aerated Stirred Tank with Double Impellers: A Generalized Correlation Including Spacing Impact - Hayder Mohammed Issa (International Journal of Chemical Engineering)
Stirred aerated tanks by double impellers are used in fermentation and various biological processes for water treatment, food industry, and pharmaceutical production. In this study, a generalized correlation model was developed for the dependent parameter (kla/N). The oxygen mass transfer from air to liquid takes place by rotating the double impellers (IBRC and PBPU) in the aerated tank. This model considers Reynolds number, Froude number, power number, the liquid height, and the spacing between impellers as the most significant specifications that are related to aerated tank performance. The spacing between the impellers is considered to be a design factor of such industrial equipment due to its remarkable impact on the oxygen mass transfer.